Genetic determinants of agranulocytosis - Dettling, Michael (Henry Stewart Talks, 2007)
Agranulocytosis, Adverse drug reactions, Etiological mechanisms, Idiosyncratic drug reactions, Genetic and immunologic background, Antipsychotic induced agranulocytosis, Clozapine, Olanzapine, Future strategies of research
Archived at 2021/02/25